KADAR INDEKS GLIKEMIK DAN HbA1C DENGAN DISFUNGSI EREKSI PADA DIABETISI DI RSUP SANGLAH DENPASAR - Ni Made Ayu Ratih Sukarini; Lely Cintari; G.A. Dewi Kusumayanti (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Abstract. Control blood sugar levels is highly recommended for prevention of Erectile Dysfunction as a complication of Diabetes Mellitus. How to control blood sugar levels is to consume low glycemic index food and check their HbA1c levels. This study aims to find a description of glycemic index and HbA1c levels with incident Erectile Dysfunction Diabetes patiens at Diabetic Centre Sanglah Hospital Denpasar. This research is an observational cross sectional study design. Samples in this study were males with diabetes who visited the Diabetic Centre Sanglah Hospital Denpasar. Data collected were analyzed using decriptive bivariate analysis. The Result showed that there are 28 samples (93,3%) eating food with a high glycemic index and 2 samples (6,7%) eating food with a low glycemic index. The result showed 14 samples (46,7%) had poor control of HbA1c levels, 10 samples (33,3%) had good control HbA1c levels and 6 samples (20,0%) had medium control HbA1c levels. The data showed 18 samples (60%) experienced Erectile Dysfunction and 12 samples (40,0%) did not experienced Erectile Dysfunction. Based on the descriction of the relationship between glycemic index and Erectile Dysfunction, 16 samples (53,3%) eating food with a high glycemic index and Erectile Dysfunction. However, 12 samples (40,0%) eating food with a high glycemic index and not have Erectile Dysfunction. According to the relationship between HbA1c levels and the incidence of Erectile Dysfunction, 6 samples (20,0%) had poor HbA1c levels and Erectile Dysfunction, but 8 samples (26,7%) had poor HbA1c levels and not have Erectile Dysfunction. And 7 samples (23,3%) who had HbA1c levels well but Erectile Dysfunction.Keywords: glycemic index, HbA1c levels, Erectile Dysfunction, patiens Diabetes